Orthodontic treatment with extraction of ectopic canine replaced by premolar - Alexandre Fausto da Veiga Jardim; Renata Araújo Silva; Taina Itana Coelho Lima; Karine Takahashi; Lucas Rodrigues Araújo Estrela; Carlos Estrela (Revista Sul-Brasileira de Odontologia, 2025)
Ectopic mandibular canines are a rare condition that has been little documented in the literature, and their treatment can be challenging for clinicians. Case report: The present article reports on the treatment of an ectopic mandibular canine (43) located transversely to the midline in the chin region in an upright patient with Class II malocclusion with biprotrusion and severe crowding. It was decided to extract the ectopic canine in the lower arch, together with the removal of three premolars, to correct the crowding without prejudice to the inclination of the incisors. As well as correcting the negative discrepancy, extraction treatment can also improve facial balance and profile. Results: After two years’ follow-up, the case is stable with satisfactory results. Conclusion: Clinicians must use their judgement to consider if orthodontic traction of a tooth in the lower arch is feasible or outweighs its cons. The replacement of a canine by the premolar in the lower arch can be achieved without aesthetic or functional compromise.